François Maspero, The Journalist: Multidirectional Activism. Issue 3 (1st December 2022) - Gabel, Aubrey
Abstract: François Maspero is best known as the owner of the radical Latin Quarter bookstore La joie de lire and the founder and editor of Éditions Maspero, but he was also a writer, a translator, and a journalist. Maspero published several novels and wrote for media outlets like Le Monde and France Culture . He wrote about his travels throughout Eastern Europe, Israel-Palestine, Algeria, and the Caribbean, and published literature reviews, obituaries, and even his testimony of the events of 17 October 1961. This article is the first comprehensive analysis of his work as a print journalist for Le Monde, notably as a travel writer. While Maspero critiqued journalism in both of his novel-travelogues, Les passagers du Roissy-Express (1990) and Balkans-Transit (1997), this article argues that his journalism was a breeding ground for his novel-writing and vice versa. The intersection between journalism, novel writing, and militancy also allowed him to create a multidirectional activism, which reanimated past militancy to understand contemporary political crises.